A UTILIZAÇÃO DOS QUADRINHOS NO ENSINO DE HISTÓRIA: AVANÇOS, DESAFIOS E LIMITES - Vilela, Marco Túlio Rodrigues (2012)
This research proposes the use of comics (comic strips; comic books and graphic novels) to teach History in Elementary Schools and High Schools. By the comics content analysis, this research will offer as suggestions on how comics can be used as historical sources to study an specific age or period as support or reference to stimulate thinking about the origins of the anachronisms found in the stereotypes and other popular images traditionally associated to past cultures. This research intends to identify which are the main difficulties, challenges or even limitations avoiding a better and more constant use of the comics as a tool to teach History.